The Role of the Union of Youth in the Life of the Youth of Uzbekistan - Sultonova, Dilnoza Abdumajidovna (European Journal of Life Safety and Stability (2660-9630), 2022)
This article will highlight the issues of creation, activities, goals and objectives of the non-governmental non-profit organization Youth Union, the role of the organization in the life of the youth of Uzbekistan, its policy to support youth.